AN EFFECTIVENESS MODEL IN EMPLOYEE PERFORMANCE WITH RIGHT TARGET RECRUITMENT AND JOB PLACEMENT POLICIE - Andika, Rindi; Hasibuan, Hasrul Azwar; Kaban, Gita Pratiwi (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2023)
This research is useful to be carried out in a company formed by the kelambir lima sub-district office in fulfilling national regulations as a manager and community service. The problem underlying this research is the policy of recruitment, selection, simultaneous and partial job placement which has a positive and significant effect on employee performance. From the results of the F test simultaneously/simultaneously the recruitment policy, selection, work placement performance of one employee at the output in the village of Kelambir Lima. employee performance. While the Test of Determination of Headjusted R square is 99.1%, the variation in performance can be explained by the independent variables from recruitment, selection, and a 1% job placement policy. by other independent variables such as compensation, leadership style and work environment.